ANALISIS NILAI TAMBAH RUMPUT LAUT SEBAGAI PRODUK PANGAN PADA KELOMPOK USAHA “ARES” KOTA MATARAM - IDA BAGUS EKA ARTIKA; IDA AYU KETUT MARINI; A. A. MADE SURYA KENCANA; IDA AYU NOPIARI; INDAH ARIFFIANTI (GANEC SWARA, 2021)
Processing raw materials into a product with higher  value added is a positive endeavor, to provide higher benefits for the welfare of society. Seaweed as one of the mainstay commodities in the West Nusa Tenggara region will provide high benefits if it is successfully processed into products with a higher selling value than if it is sold as a ra product. This study aims to determine the  value added  of processed food products made from seaweed, namely seaweed rengginang,  seaweed kripik and seaweed crackers which are processed by the "ARES" Business Group in Karangbaru Village, Mataram City. The research method is descriptive, and value added analysis is based on the Hayami Method. From the calculated of value added , it turns out that the value added of seaweed kripik produces the highest value added, which is Rp. 111,400,- per kilogram of processed seaweed, then the  value added of seaweed crackers is Rp. 98.000, - and the added value of seaweed rengginang  is Rp. 78,050,- Furthermore, it is suggested to the “ARES” Business Group if the demand for seaweed kripik is relatively good, the production of seaweed kripik needs to be increased in capacity in the future, and the “ARES” Business Group to continue to be creative in making products made from seaweed to be processed into superior products, as an effort to increase the  value added of raw materials into products with higher value added